2022
DOI: 10.1021/acsami.2c11423
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent COFs with a Highly Conjugated Structure for Combined Starvation and Gas Therapy

Abstract: Covalent organic frameworks (COFs) show great potential in biomedicine, but the synthesis of fluorescent ones with a highly conjugated structure in mild conditions remains a challenge. Herein, we reported a facile method to synthesize a nanosized, highly conjugated, and N-enriched COF material with bright fluorescence and further integrated it as a novel nanoplatform for efficient cancer starvation/gas therapy. High surface area and a porous structure endowed COFs with large loading capacity for both glucose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Molecular gas therapy has exhibited promising outcomes in a variety of diseases including CLI. [52,53] With this ). Limb ischemic tissues were injected intramuscularly with UIO-66-NH 2 , UIO-66-NH 2 @GYY4137, UIO-66-NH 2 @BMP6, and UIO-66-NH 2 @GYY4137@BMP6 nanoparticles, respectively.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Molecular gas therapy has exhibited promising outcomes in a variety of diseases including CLI. [52,53] With this ). Limb ischemic tissues were injected intramuscularly with UIO-66-NH 2 , UIO-66-NH 2 @GYY4137, UIO-66-NH 2 @BMP6, and UIO-66-NH 2 @GYY4137@BMP6 nanoparticles, respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Molecular gas therapy has exhibited promising outcomes in a variety of diseases including CLI. [ 52,53 ] With this strategy, this work demonstrated the therapeutic potential of exogenous BMP6 to augment the efficacy of H 2 S by modulating YAP/TAZ and Jun‐related pathways. Moreover, we proved that the novel UIO‐66‐NH 2 @GYY4137@BMP6 dual‐delivery system could promote angiogenesis and inhibit oxidative stress, thus ameliorating the impairment of CLI.…”
Section: Discussionmentioning
confidence: 96%
“…14,16 Moreover, efforts are made to make full use of the advantages of COFs in their modifiability with different functional groups, 17,18 which allows the postsynthetic modification to achieve tailored properties, including proton conductivity, 19,20 photocatalytic activity, 21,22 and fluorescence characteristic. 23,24 For instance, recent research studies have shown that postmetallized COFs can be used for electrocatalysis, 25,26 water decomposition, 27,28 and CO 2 reduction. 29,30 In these reports, metal ions were strategically modified on COFs, which could remarkably improve the performance of the materials and play important roles in enzymatic catalysis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Covalent organic frameworks (COFs) have gained significant attention due to their stable covalent bonds and remarkable properties, such as high chemical stability, large specific surface area, excellent biocompatibility, and customizable constituent units. These unique characteristics endow COFs with high versatility for various applications, including gas storage, , catalysis, , environmental remediation, ,, bioimaging, , drug delivery, , and biosensing. , Recently, significant efforts have been devoted to preparing uniform COF nanoparticles (COF NPs), and the improved tunability and bioavailability can boost the biomedical applications of COFs. , Moreover, efforts are made to make full use of the advantages of COFs in their modifiability with different functional groups, , which allows the postsynthetic modification to achieve tailored properties, including proton conductivity, , photocatalytic activity, , and fluorescence characteristic. , For instance, recent research studies have shown that postmetallized COFs can be used for electrocatalysis, , water decomposition, , and CO 2 reduction. , In these reports, metal ions were strategically modified on COFs, which could remarkably improve the performance of the materials and play important roles in enzymatic catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Covalent organic frameworks (COFs) are highly crystalline materials composed of light elements, known for their regular pores and specific functional groups within these pores. COFs were first introduced in 2005 with the synthesis of COF-5 1 by Yaghi, and since then, a wide range of two-and threedimensional COFs have been synthesized and applied in various fields such as gas separation, 2-5 catalysis, [6][7][8] fluorescence detection, 9,10 drug delivery, [11][12][13] and batteries. [14][15][16] In the realm of 2D COFs, the topology of the material is typically dictated by the symmetry of the involved building blocks, [17][18][19] representing the energetically favored state.…”
mentioning
confidence: 99%